A Partitioned Equilateral Triangle

Geometry Level 3

Above shows an equilateral triangle A B C ABC with side length 1. Given that M , N M, N and Q Q are points on the sides A B , B C AB, BC and A C AC such that the lines A N , B Q AN, BQ and C M CM divide the triangle into 4 triangles and 3 quadrilaterals.

We color the triangles in two colors (orange and green) in such way that any two triangle with a common vertex are colored with different colors.

If the area colored in green is equal to that colored in orange, find the value of A M + B N + C Q AM+BN+CQ .


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Oct 28, 2018

Let A M AM , B N BN and C Q CQ be x x , y y and z z respectively. We need to find x + y + z x+y+z , let the area of the equilateral triangle be a a .

Because the side length of equilateral A B C \triangle ABC is 1, the area of A B N \triangle ABN , [ A B N ] = y a [ABN]=ya and that of green A P M \triangle APM , [ A P M ] = x y a [APM]=xya . Similarly, [ B N R ] = y z a [BNR]=yza and [ C Q S ] = z x a [CQS]=zxa . Therefore, the area of the three green triangles is ( x y + y z + z x ) a (xy+yz+zx)a .

The area of the orange P R S \triangle PRS is given by:

[ P R S ] = [ C B M ] [ P N B M ] [ C N R S ] = [ C B M ] ( [ A B N ] [ A P M ] ) ( [ B C M ] [ C Q S ] [ B N R ] ) = ( ( 1 x ) ( y x y ) ( z z x y z ) ) a = ( 1 x y z + x y + y z + z x ) a \begin{aligned} [PRS] & = [CBM] - {\color{#3D99F6}[PNBM]} - {\color{#D61F06}[CNRS]} \\ & = [CBM] - {\color{#3D99F6}([ABN]-[APM])} - {\color{#D61F06}([BCM]-[CQS]-[BNR])} \\ & = \big((1-x) - {\color{#3D99F6}(y-xy)} - {\color{#D61F06}(z-zx-yz)}\big)a \\ & = (1-x-y-z+xy+yz+zx)a \end{aligned}

Since the area in green is equal to that in orange, we have:

( x y + y z + z x ) a = ( 1 x y z + x y + y z + z x ) a 0 = 1 x y z x + y + z = 1 \begin{aligned} (xy+yz+zx) a & = (1-x-y-z+xy+yz+zx)a \\ 0 & = 1-x-y-z \\ \implies x+y + z & = \boxed 1 \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...